A review of the comprehensive clinical treatment and nursing interventions for elderly female urinary incontinence patients (老年女性尿失禁患者综合性临床治疗与护理的研究进展) - ZHANG Anyi (张安逸); LI Jun (李俊); SUN Mengnan (孙梦楠) (中西医结合护理)
Th　is review summarized the current status of domestic and international research on epidemiology, evaluation, treatment and nursing interventions for elderly female urinary incontinent patients. This review would also provide a theoretical basis for further developing to build up total quality management system in elderly female urinary incontinent patients. (本研究从流行病学, 尿失禁的评价标准, 老年女性UI患者的综合治疗及护理等方面, 综述了老年女性UI患者国内外研究现状, 并对现有治疗及护理干预措施进行归纳总结, 为构建老年女性UI患者全程管理体系提供依据。)